Proyecto técnico y económico para la implementación de un taller multiservicio en la Cooperativa de taxis “Alianza” del cantón Quevedo, año 2014 - Intriago Zambrano, Ricardo Fernando (2015)
The taxi cooperative "Alliance" is one of the oldest institutions in the city of Quevedo, was created under Ministerial Agreement No 0165 of March 24, 1972, giving a service to the public with quality and warmth. The general objective to develop a technical and economic project for the implementation of a multi-workshop at the taxi cooperative "Alliance" which meets the technical and economic requirements of the members of the cooperative, it began with the contextual part is the approach objectives, and hypotheses. The second chapter covers the theoretical support of authors and researchers, which provide the necessary technical guidance for having carried out this research. Then we have the third chapter is the methodology used in this investigation. The fourth chapter is the most important find since the results and analysis of the investigation, it was determined through surveys the opinions of the partners tell their maintenance requirements of its units, which 64% of them support the creation of a multi-workshop at the headquarters of the cooperative ,; also the number of workers that would integrate the workshop (7) seven employees, tools and equipment to be used and finally the technical and economic feasibility of the proposal, which I throw if feasible, since the market share was determined, as the technical and economic. After analyzing the situation of the company from the view point from partner and manager of the cooperative, these mainly (91%) agree with the implementation of a workshop.